Health Literacy of Unhealthy Diet Consumption in Thailand - Suriya, Sitaporn; Torut, Buraskorn (Makara Journal of Health Research, 2024)
Background: The burden of noncommunicable diseases (NCDs) is increasing worldwide, including in Thailand. One risk factor for NCDs is an unhealthy diet. Thus, this study aimed to investigate the factors affecting the consumption of an unhealthy diet and determine the proactive policies that support factors inhibiting an unhealthy diet. Methods: We investigated the factors affecting unhealthy diet consumption behavior by multiple linear regression analysis by surveying 970 Thai patients with early-stage NCD. In addition, we investigated appropriate policy proposals by conducting in-depth interviews with 20 key informants. Results: Knowledge (−0.247, 95% confidence interval (CI) −0.285 to −0.210), family and reference person (−0.170, 95% CI −0.275 to −0.065), health awareness (−0.111, 95% CI −0.148 to −0.074), and education (−0.062, 95% CI −0.092 to −0.032) were significantly related to the inhibition of unhealthy diet consumption. Four proactive policies supporting those factors include the following: (1) reforming the national curricula to include scientific knowledge and health literacy, (2) educating social influencers to help advocate accurate information, (3) creating an easily accessible public food database, and (4) designing consumer-friendly front-of-package labels. Conclusions: Although strengthening health literacy involves many factors and requires cooperation from many sectors, it may be a solution for a sustainable fight against NCDs.